2008
DOI: 10.1590/s0037-86822008000600002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human herpesvirus-7 by qualitative nested-PCR: comparison between healthy individuals and liver transplant recipients

Abstract: Diagnosis of human herpesvirus-7 active infection in transplant patients has proved difficult, because this virus is ubiquitous and can cause persistent infections in the host. The significance of viral DNA detected in leukocytes by PCR is unclear and cross-reaction in serological tests may occur. This study aimed to evaluate nested-PCR to detect human herpesvirus-7 active infection in liver transplant recipients compared to healthy individuals. human herpesvirus-7 nested-PCR was performed on leukocytes and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…HHV coinfection was considered in case of two or more positive HHV-DNA results in the same serum sample. The following isolated and/or combined symptoms were used to characterize active HHV infection, and/or likely HCMV disease: fever, headache, abdominal pain, seizure, changes in behavior, low levels of consciousness, mental confusion, motor dysfunction, neuropathy, paresthesia, drowsiness, vomiting, weakness, weight loss, myoclonus, memory loss, visual and psychomotor impairment, genital and orofacial herpesvirus, ocular infection, dermatitis, varicella, mononucleosis syndrome, Burkitt's lymphoma, nasopharyngeal carcinoma, Hodgkin's disease, HCMV colitis, retinitis, hepatitis, pneumonitis, roseola infantum or exanthem subitum, Kaposi's sarcoma, primary effusion lymphoma and Cattleman's disease [27][28][29][30][31][32].…”
Section: Criteria For Confirming Hhv Infection or Likely Hcmv Diseasementioning
confidence: 99%
“…HHV coinfection was considered in case of two or more positive HHV-DNA results in the same serum sample. The following isolated and/or combined symptoms were used to characterize active HHV infection, and/or likely HCMV disease: fever, headache, abdominal pain, seizure, changes in behavior, low levels of consciousness, mental confusion, motor dysfunction, neuropathy, paresthesia, drowsiness, vomiting, weakness, weight loss, myoclonus, memory loss, visual and psychomotor impairment, genital and orofacial herpesvirus, ocular infection, dermatitis, varicella, mononucleosis syndrome, Burkitt's lymphoma, nasopharyngeal carcinoma, Hodgkin's disease, HCMV colitis, retinitis, hepatitis, pneumonitis, roseola infantum or exanthem subitum, Kaposi's sarcoma, primary effusion lymphoma and Cattleman's disease [27][28][29][30][31][32].…”
Section: Criteria For Confirming Hhv Infection or Likely Hcmv Diseasementioning
confidence: 99%
“…However, nested PCR carried out in DNA extracted from serum can be considered more speci¢c than PCR carried out in DNA extract from whole blood or peripheral blood leukocytes (9). A previous study conducted in our center showed that nested PCR in serum, according to the method described in this paper, did not detect latent infection in a healthy cohort (12). Serum samples that presented b-globin gene ampli¢cation were excluded from this study, and the presence of HHV-7 DNA in serum as a result of cell lysis is therefore unlikely.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, IgM against HHV-7 was found in all samples contributing to the hypothesis of true active infection had occurred. Since that this method did not detect latent infection in previously study (Thomasini et al, 2008) and blood was collected before surgery, it could be explained by reactivation caused by underlying liver disease or by transient viremia. Although some syndromes related to HHV-7 in immunocompetent patients have been described (Ward et al, 2005), studies in pre-transplant time should be performed to evaluate each hypothesis.…”
Section: Discussionmentioning
confidence: 86%
“…In our center, we found that nested-PCR carried out in DNA extracted from sera did not detect latent HHV-7 in a healthy cohort (Thomasini et al, 2008). In addition, positive IgM anti-HHV-7 and/or significant increase in IgG anti-HHV-7 titers were correlated with positive nested-PCR for HHV-7 in adult liver transplant recipients (Peigo et al, 2009).…”
Section: Human Herpesvirusmentioning
confidence: 91%